Sinus Histiocytosis with Massive Lymphadenopathy (Rosai-Dorfman Disease): A Case Report and Literature Review - Pradhananga,Rabindra Bhakta (2014)
Introduction Rosai-Dorfman disease (RDD) is a rare histiocytic proliferative disorder of unknown etiology. Usually it presents with massive painless cervical lymph node enlargement. Histologically, it shows proliferation of distinctive histiocytic cells that demonstrate emperipolesis in the background of a mixed inflammatory infiltrates. Immunohistochemically, the cells are positive for markers such as CD68 and S100. Objective To report a case of a 12-year-old patient with multiple sites of cervical lymphadenitis, which was diagnosed as RDD histopathologically as well as immunohistologically. Resumed Report A 12-year-old girl presented with multiple painless sites of cervical lymphadenitis without any systemic and other ear, nose, and throat manifestations. The biopsy report of the lymph node showed dilatation of the sinuses, filled with histiocytes having foamy cytoplasm. Many of the histiocytes were engulfing mature lymphocytes. The sinus histiocytes were strongly positive for S-100 protein. Conclusion RDD must be considered in the differential diagnosis of massive or multiple lymphadenopathies.